High Detection Performance of NDIR CO2 Sensor Using Stair-Tapered Reflector - Han, Ji-Hoon; Han, Sang-Wook; Kim, Se Min; Pak, James Jungho; Moon, Sung (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2013)
In this paper, we propose tapered reflectors having stair-like structures that focus scattered infrared (IR) rays to enhance the detection performance of a non-dispersive IR (NDIR) CO2 sensor. We demonstrate that the sensitivity of the output voltage is increased by 2 and 1.27 times in simulations and experiments, respectively, compared with the case when conventionally tapered reflectors are used. Through applying a stair-like structure inside the tapered optical cavity, scattered IR rays are condensed, and more accurate CO2 concentration measurements are possible. In addition, we show that the output voltage changes only slightly with temperature and humidity variations compared with the conventionally tapered optical cavity. Because the proposed structure can be applied to any type of optical cavity without major modifications, we expect that it can resolve the performance limitations of low-end NDIR gas sensors.
Keywords: GAS SENSORS; DESIGN